2020
DOI: 10.1111/aji.13231
|View full text |Cite
|
Sign up to set email alerts
|

Association among placental 11β‐HSD2, PPAR‐γ, and NF‐κB p65 in small‐for‐gestational‐age infants: A nested case‐control study

Abstract: Problem: 11β-Hydroxysteroid dehydrogenase 2 (11β-HSD2) catalyzes active glucocorticoids into their inactive products, preventing the passage of glucocorticoids into the fetus from maternal circulation. Peroxisome proliferator-activated receptor (PPAR)γ is a member of the nuclear receptor superfamily that regulates the expression of placental 11β-HSD2. Nuclear factor-kappa B (NF-κB) is a transcription factor that regulates inflammatory signaling. This study aimed to investigate the association among 11β-HSD2, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(50 reference statements)
1
5
0
1
Order By: Relevance
“…This implies that placental infection-induced inflammation is associated with lower placental weight. As mentioned above, the increase in pro-inflammatory cytokines, and activation of the components of the inflammasomes cascade, is consistently reported in pregnancies associated with placental inflammation [17,37,[47][48][49][50][51][52][53][54][55][56][57][58][59]. This study demonstrates that the reduction of placental weight and birth weight in FGR may be associated with sterile inflammation, specifically when there are no signs of infection associated with the FGR placentae included in this study.…”
Section: Discussionsupporting
confidence: 71%
“…This implies that placental infection-induced inflammation is associated with lower placental weight. As mentioned above, the increase in pro-inflammatory cytokines, and activation of the components of the inflammasomes cascade, is consistently reported in pregnancies associated with placental inflammation [17,37,[47][48][49][50][51][52][53][54][55][56][57][58][59]. This study demonstrates that the reduction of placental weight and birth weight in FGR may be associated with sterile inflammation, specifically when there are no signs of infection associated with the FGR placentae included in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Placental 11β‐HSD2 inactivates maternal glucocorticoids, and its expression is regulated by PPARγ. In a study of SGA and AGA newborns (Fu et al, 2020), placental 11β‐HSD2 was lower in SGA than in AGA placentas. Inflammatory cytokines were higher in placentas from SGA infants.…”
Section: Resultsmentioning
confidence: 95%
“…[8][9][10] Inflammation has been proposed to be a responsible factor. 11 Less cortisol is thus metabolized to cortisone, which does not activate the cortisol receptor. Increased cortisol release in response to stress decreases choline concentrations, presumably by causing the liver and other organs to sequester choline as phosphatidylethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several risk factors for SGA have been identified in observational studies including increased cortisol levels, increased inflammation often measured as increased maternal C-reactive protein (CRP), and female fetal sex. [7][8][9][10][11][12][13][14][15][16] Maternal nutrition has not generally been considered as a risk factor or as a preventative intervention. However, recent studies have shown effects of choline and its metabolite betaine on birth weight.…”
mentioning
confidence: 99%